System-based reliability analysis of stainless steel frames under gravity loads. (15th March 2021) - Arrayago, Itsaso; Rasmussen, Kim J.R.
Highlights: Extension of the Direct Design Method to stainless steel structures is presented. Rigorous reliability framework is built for stainless steel structures. Six stainless steel portal frames are analysed, covering different families. Reliability indices are presented for different design frameworks under gravity loads. System γ M, s and ϕ s factors are proposed for different target reliability indices. Abstract: Current structural codes for steel and stainless steel structures such as AISC 360-16, AISC 370-21, AS/NZS 4100 and Eurocode 3 are based on the traditional two-step member-based design approach, in which internal actions are first obtained from a structural analysis, usually elastic, and the strength of each member and connection is subsequently checked using a structural design standard. However, the most recent versions of these standards already incorporate preliminary versions of the direct, or one-step, system-based design alternative, which is based on the design-by-analysis concept and allows evaluating the strength of structures directly from numerical simulations, although the standards in their current form do not provide reliability requirements for structural systems. Therefore, it is necessary to build a rigorous structural reliability framework to investigate acceptable target reliability indices for structural systems and to provide adequate system safety factors and system resistance factors. While this framework has been developed based on advanced Finite Element analysis for hot-rolled and cold-formed carbon steel structures in recent years in the form of the Direct Design Method (DDM), the framework does not exist for stainless steel structures. This paper presents an extension of the DDM to the analysis of stainless steel structures, in which system reliability calibrations are presented for six stainless steel portal frames under gravity loads covering the three most common stainless steel families and different failure modes using advanced numerical simulations. From the derived reliability calibrations, suitable system safety factors γ M, s and system resistance factors ϕ s are proposed for the direct design of stainless steel frames in the European, US and Australian design frameworks under gravity loads.